Bilateral ureteral obstruction due to aorto-iliac aneurysm - Olivera, Daniel; Bergalli, Luis; Carriquiry, Luis A.; Mate, Miguel; Mazzuchi, Nelson; Caropale, Nelson; Tiscornia, Eduardo; Rocha, Osvaldo; Petrucelli, Dante (Cirugía del Uruguay, 1978)
The authors report a case of bilateral obstruction of ureters due to aorto-iliac aneurysm causing renal insufficiency Surgery was performed entailing vascular replacement and ureter liberation; immediate clinical and radiologic evolution was good. A review of literature on the subject is included in the paper. The authors stress the importance of a correct nephro- urologic evaluation prior to surgery, in systematic surgery of abdominal aorta and in particular, of aneurysms. Arterial replacement with ureter liberation is considered elective treatment.